The movement of historically informed performance in the context of the culture of the XX-XXI century - M-M. V. Ljubiva, (Ukrainian Cultural Studies, 2020)
The hermeneutical method is the basis for performing interpretation, because the author's musical text is the initial condition for its implementation. Over the last century, new musical forms and performing practices have emerged, where there is a synthesis of the heritage of many stylistic eras. Modern trends in performance art can be divided into three global independent areas – actualization, authenticity and avant- garde. The orientation in modern performance is directed both at the historical authenticity of the performance and at the questions of the subjective potency of musical creativity. There is an affirmation of a new paradigm, which consists in increasing the role of the intellectual principle, in striving to study a musical work in the context of the epoch that created it, in clearing the traditions of performance from later layers. Due to the growing interest of musicians in Renaissance and Baroque music, the number of soloists and groups performing Western European works written before the middle of the XVIII century is increasing. Over the course of the century, there has been a change in the status of authentic performance from individual to universal and social, because it not only organizes the experience of the community of musicians, but also forms the consciousness of a whole generation of culture.Due to the fact that a person is aware of the loss of the integrity, traditional art forms undergo transformations and destruction, which caused the need to appeal to the Baroque culture. The reception of the Baroque culture promotes the restoration of cultural identity, warns against multicultural fragmentation, and creates conditions for establishing links between cultural eras. The Baroque aesthetic is becoming one of the defining markers of popular culture.Attempts to adequately reproduce musical impressions of past eras among performers and interest in them among the public is a significant characteristic of modern society. A comprehensive study of authentism as a direction allows us to understand the context and functions of music for the cultural types of that time.
Keywords: music, culture, historically informed performance, authentism, interpretation